MONOPOLI KEPEMILIKAN MEDIA & LENYAPNYA HAK PUBLIK - Karman, Karman (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
This article will discuss about how practice of monopoly conducted by media corporates and the effect to audience. I explain this matter by elaborating cases of the monopoly in Americaâs media and Indonesia one. Cases may change and be different between past time and now. However, the concept of monopoly and characteristics of the media as an economy or business institution are the same. Media tend to concentrate the ownership or monopoly in order to be dominant. The real goal of media are money or profitability and influence. Ideally, media must ensure the diversity of media ownership both structurally organizationally. Culturally, media must prioritize the plurality of content. Mass media should also be a public sphere. The lack of diversity of media owners can be a barrier to create plurality of media content. Accordingly, media is only a apparatus/tool for both media elites and political party elites, not for public interest. Media watchdogs (e.g., Indonesian Broadcasting Commission and The Indonesian Press Board) should be more critical in evaluating media content in order to be more oriented to public interest, not for vested interest.